العقائد الإيمانية وعلاقتها بمفهومي النصر والتمكين - برديني، عدنان احمد العبد (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2013)
Within its theoretical frame, this study aims at distinguishing between the theological reasons of victory and the theological reasons of authoritative establishment (empowerment). Then it explains how victory and authoritative establishment are partially related to theological beliefs in terms of their branches and subdivisions, and how they are also generally related terms of which are six principles, while revealing the relativity in achieving victory and authoritative establishment, and clarifying their relationship with achieving theological beliefs. In order to clarify this relationship the researcher relied on a collection of practical applications, which were centred on studying a number of battles during which both victory and authoritative establishment were achieved for a number of prophets such as Nuh, Ibrahim, Musa and Eesa (may peace be upon them all). This is followed by a study of three of the battles during which both victory and authoritative establishment were achieved at the time of our prophet Muhammadd (may Allah exalt his mention); namely: the Battle of Badr, the Battle of Al-Fateh, and the Battle of Hunayn. In order to clarify the relationship that victory and authoritative establishment have with theological beliefs, the researcher relied on the induction method through gathering Qur'anic verses, and authentic narrations of the Prophet and his companions which mention these events and battles. The researcher then analyzed them and derived the most prominent theological beliefs that are manifested therein by applying the inductive method. Finally, the researcher applied the comparative method to apply a specific comparison between the theological beliefs achieved during the Battle of Badr, and the theological beliefs achieved during the Battle of Hunayn, while revealing the extent of achieving those theological beliefs compared to the extent of achieving victory and authoritative establishment. He then made a general comparison between victory achieved for previous prophets and their followers and that which was achieved for the Muslims. This study reached a number of conclusions, the most important of which are: The percentage of theological beliefs required to achieve victory is different than the percentage of theological beliefs required for authoritative establishment; the extent of achieving victory is proportionally correlated with the extent of achieving theological beliefs. As for authoritative establishment, the researcher views that it was on battles achieved at all before full implementation of theological beliefs when the battle took place. Furthermore, the utilization of material on reasons to achieve victory and authoritative establishment is not independent of utilizing theological reasons to achieve each of the two.